Formation mechanism of basalt-related agate deposits: an example from the Ating River alluvial gravels in the Xunke area, Heilongjiang, NE China - Zhang, Peng; Wang, Bo-Chao; Zheng, Ji-Lin; Guo, Xiao-Yu (Frontiers in Earth Science, 2025)
This study investigates Xunke agates from Ating River alluvial gravels (Northeast, NE China) using optical microscopy, electron probe microanalyzer mapping (EPMA), and laser ablation–inductively coupled plasma–mass spectrometry (LA–ICP–MS) to constrain the formation mechanisms of basalt-hosted agate deposits. Xunke’s secondary gravel agates are genetically associated with Early Cretaceous Ganhe (GH) Formation basalts in Mesozoic fault-depression basins. The basalt serves as the primary ore-forming fluid reservoir. Two distinct structural sequences are found. Type I (colloform–cryptocrystalline–fibrous–crystalline quartz) reflects rapid cooling-induced fluid mixing, evidenced by the co-enrichment of Na-K-U-Ge in crystalline layers (U up to 1.541 ppm) indicative of a sustained low-temperature acidic condition in the ore-forming fluid. Type II (micro-granular–fibrous–crystalline quartz(–fibrous)–cryptocrystalline–crystalline quartz) forms at a higher temperature, marked by micro-granular texture chalcedony initial layers. There is a depletion of Al-K-Na in the spherulitic layers and Ge depletion (0.24 ppm) in Type II’s nucleation layers. Si and Ti-Ga-Ge substitution coupled with Ce and Eu negative anomalies fingerprint hybrid fluids mixing magmatic (basalt-derived) and meteoric components. Outer-to-inner Hf depletion (0.24→0.07 ppm) tracks fluid evolution toward lower H2O content and higher acidity. Band redness correlates with Fe concentration gradients (4,635→1.202 ppm), controlled by oxidation state fluctuations.